Development of an Auditing Tool for Clinical Occupational Health Services: A Modified Delphi Technique - Wanasathop, Patrawan; Chaiear, Naesinee; Koonmee, Supinda (Biomedical Sciences and Clinical Medicine, 2025)
Objective This study aim to develop a comprehensive auditing tool for clinical occupational health services (OHS) in corporate settings. Methods The design used a modified Delphi technique. The study was comprised of four steps: questionnaire construction and panelist selection, two rounds of questionnaires, and consensus determination. The participating experts included 31 occupational health professionalsfrom 7 countries, representing management, occupational medicine, and auditing roles. Two rounds of questionnaires were administered to achieve 80.0% agreement on essential activities across the 7 key domains. Results The Delphi process yielded an audit tool encompassing 62 activities across seven domains: policy management (4 activities, 100.0% consensus), fitness for work assessment (7 activities, 85.7% consensus), medical surveillance programs (13 activities, 100% consensus), return to work assessment (7 activities, 71.4% consensus), occupational disease management (10 activities, 80.0% consensus), medical emergency preparedness (15 activities, 86.9% consensus), and health promotion (6 activities, 66.7% consensus). Experts’ backgrounds influenced their focus, with hospital- based physicians emphasizing clinical protocols, company-based practitioners stressing implementation, management prioritizing governance, and auditors ensuring comprehensive assessments. Conclusions This auditing tool required consideration of 7 domains, where experts rated the policy management and medical surveillance processes as the most important, whereas the domain of health promotion had the lowest importance score. This tool can help guide organizations in strengthening the foundational domains of OHS.